Pengembangan Media IPAS Berbasis Google Sites Untuk Meningkatkan Hasil Belajar Siswa Kelas V SD - Diah Windi Widyawati; Imam Sujono; Nafik Umurul Hadi (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to develop a learning medium based on Google Sites for the Natural and Social Sciences (IPAS) subject in Grade V at SD Negeri 2 Kedungsoko, and to examine its feasibility, practicality, and effectiveness in improving student learning outcomes. The research employed a Research and Development (R&D) design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Participants included subject matter experts, media experts, an IPAS teacher, and Grade V students. Data were collected through validation sheets, teacher and student response questionnaires, and pretest–posttest assessments, then analyzed using descriptive quantitative methods and inferential statistics (normality test, t-test, and N-Gain analysis). The validation results indicated that the media was highly feasible (92.5% from subject matter experts and 96% from media experts). The practicality was rated highly by both the teacher (93.33%) and students (98.3% in the small group; 91.3% in the large group). The t-test showed a significant difference between pretest and posttest scores (p < 0.05), with average N-Gain values of 0.709 (small group) and 0.70 (large group), both categorized as high. These findings suggest that Google Sites is an effective digital learning medium to enhance the cognitive achievement of elementary school students